2020
DOI: 10.3390/ma13071793
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol Prodrugs with Antimicrobial Activity Loaded on Clay Nanocomposites

Abstract: Background: Carvacrol, an essential oil with antimicrobial activity against a wide range of pathogens, and its water soluble carvacrol prodrugs (WSCP1-3) were intercalated into montmorillonite (VHS) interlayers to improve their stability in physiological media and promote their absorption in the intestine. Methods: Intercalation of prodrugs by cation exchange with montmorillonite interlayer counterions was verified by X-ray powder diffraction and confirmed by Fourier transform infrared spectroscopy and thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The strong antimicrobial activity of T. decussatus could be attributed to the major compounds of the EO, such as carvacrol and p -cymene. Several studies reported the antimicrobial activity of carvacrol and p -cymene [ 59 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The strong antimicrobial activity of T. decussatus could be attributed to the major compounds of the EO, such as carvacrol and p -cymene. Several studies reported the antimicrobial activity of carvacrol and p -cymene [ 59 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…After centrifugation at 10,000 rpm, the solid hybrids were recovered and dried for subsequent investigations. To quantify the amounts of T1-3 retained by the HAL powder, supernatants were examined as previously reported by High-Performance Liquid Chromatography (HPLC) [ 15 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…They showed antimicrobial activities and increased water solubility compared to CAR ( Table 1 ) [ 14 ]. In our previous works, hybrids of T1-3 and layered montmorillonite or fibrous palygorskite and sepiolite were formulated to obtain their sustained release in the target site [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As reported by the World Health Organization (WHO), antibiotics are becoming progressively ineffective as drug resistance extends worldwide leading to infections that are difficult or impossible to manage [1]. Several reasons are responsible for AMR such as an inappropriate use of antibiotics, microbial behavior, gene transfer, or antioxidant, and wound healing properties [22]. It is a good antibacterial agent against both Gram-positive and -negative bacteria exerting its antimicrobial activity by disrupting bacterial membrane, bacterial lysis, and leading to leakage of intracellular contents.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceuticals 2022, 14, x FOR PEER REVIEW 3 of 18 pathogens (Figure 1). Notably, carvacrol was chosen as the phytochemical component to conjugate to the series of cinnamic acids helpful by virtue of its wide natural antimicrobial, antioxidant, and wound healing properties [22]. It is a good antibacterial agent against both Gram-positive and -negative bacteria exerting its antimicrobial activity by disrupting bacterial membrane, bacterial lysis, and leading to leakage of intracellular contents.…”
Section: Introductionmentioning
confidence: 99%